Law Enforcement Against Bank Account Breach by Hackers in Perspective of Legal Law - Ndruru, Donius; Esther, July; Debora, Debora (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2025)
The development of information and communication technology has changed the landscape of the financial industry, particularly in digital banking. Despite offering convenience to customers through services such as internet banking and mobile banking, the risk of cybercrime, such as account breaches, is increasing. This research aims to analyse law enforcement against hackers in cases of bank account break-ins in Indonesia. The method used is a normative legal approach, which involves the study of library materials through a statutory and case approach. Data sources include primary, secondary, and tertiary legal materials, which are analysed descriptively to understand relevant legal norms and doctrines. This research found that despite the existence of various laws related to personal data protection and cybercrime, challenges in law enforcement remain, including a lack of public awareness and adequate human resources. In recent years, bank account breaches have become more prevalent, with various modes that are increasingly sophisticated and difficult to detect. Real-life cases, such as the arrest of 35-year-old Palembang-born porters and hacker syndicate member Gerri Harri Wijaya, serve as important examples in highlighting the need to improve customer protection and banking system security. To stop similar atrocities, more public education and awareness is needed. The results of this study are expected to provide insights for the government, law enforcement agencies, and the banking sector in creating a safe environment for digital financial transactions, as well as raising public awareness about the risks of cybercrime.